Desempenho da Tecnologia de Filtração em Múltiplas Etapas (FiME) no Tratamento de Águas de Abastecimento em Escala Piloto - CAMPLESI, Daniela Cristina Fonseca (2009)
The present work has evaluated the efficiency of an MSF system for treating supplying water on a pilot scale. A MSF pilot plant was located in the Water Treatment Station (WTS) area in Goianápolis- GO and fed by Sozinha stream. The plant was comprised of a dynamic prefilter (DPF) and a vertical upflowing pre-filter (VUF) in layers, both of them with different granular compositions; a slow sand filter (SSF); and a slow sand filter with activated carbon (SSFAC), which was called SEQ. 1. The second sequence of the trial, SEQ. 2, was comprised of a dynamic pre-filter (DPF) and a slow sand filter (SSF-2). The filtration rates in use were 24 and 48 m3/m2 a day for DPF, 12 e 24 m3/m2. day for APF; 3 e 6 m3/m2. day for SSF and SSFAC. The efficiency was evaluated by analyzing turbidity, apparent color, total suspended solids (TSS), as well as total thermo tolerant coliforms. The following items were evaluated: the filtration rates ranging effect onto the MSF unit trial system efficiencies; the MSF system efficiency comparison to the WTS complete cycling treatment; and the correlations between turbidity, color, and coliforms removals and the TSS removals. The results obtained from the trials have shown that DPF and VUF are important units for microorganisms and solid particles retaining, for it prepares the effluent in order to submit it into slow filtration. They have also shown that they make it possible for the roughing filtration to last longer. Generally put, it presents that the slow filters are significantly and above 90% efficient in removing TSS, color and turbidity, and 99% efficient in removing total coliforms and thermotolerant coliforms in all roughing filtration. After comparing the quality of both the water produced by MSF and the one by the complete cycling WTS, it was noticed that MSF produces water with quality similar to the complete cycling WTS. The range for the filtration rates has had significant influence only in the removal efficiencies of color and turbidity. There isn t correlation among the removals of the parameters color, turbidity, TSS and coliforms but for the correlation among apparent color and true color. The experiment results suggest that MSF technology, when suitably operated, it is a viable system for the treatment of supplying water and produced water with low levels of color, turbidity, TSS and coliforms is that 40% of the samples, provided drinking water under conditions compatible to those established by Decree 518/2004 of the Ministry of Health (BRAZIL, 2004) for human consumption